Mortalités printanière et estivale de l'huître creuse C. gigas en élevage à plat dans le bassin de Marennes-Oléron. Etude du métabolisme du glycogène sur différentes origines de cheptels - Faury, Nicole; Remoue, Sophie; Soletchnik, Patrick; Goulletquer, Philippe; Geairon, Philippe; Le Moine, Olivier; Razet, Daniel; Guilpain, Patrice; Robert, Stephane; Taillade, Sylvie (2001)
This study aims to assess the broodstock origin and cultural effects on oyster summer mortality rates. Three oyster batches, two originating from the Marennes-Oléron Bay, and one from the Normandy rearing area were deployed in March 2000 on the Ronce Perquis oyster bank, on experimental site since 1996. On bottom cultured oysters were monitored until January 2001. By the end of the experiment, the cumulative mortality ranged from 51 to 58 %. Following on initial mortality rate (8.8 % to 9.3 %), oyster batches showed a critical period early July. In 15 days, mortality rate reached 13.7 %. Over the rearing period, the oyster shell growth ranged between 8.9 g and 12.7 g. The somatic gain represented 0.44-0.48 g of dry meat weight. Spawning event occured in August for the oldest batch from Marennes-Oléron, and was the largest compared to other batches. For the 2 other oyster batches (3 years'old), spawning occured during th e 2 first weeks of August. At the experiment initiation, the oyster batch from Normandy showed highest Iipids (7.5 %) and carbohydrates (10.5 %) concentration s, greater than the Charentais batches. Two and three months were required to obtain a similar carbohydrates and Iipid concentrations for those 2 charentais batches (8.5 and 10%). Early June, lipogenesis slowed, as weil as the gametogenesis for the 3 batches. Metabolism showed a disfun ctionning in Ju ly with the lowest carbohydrates concentrations (4 %), one month before spawning. To susta in their metaboli sm, lipids were used by the oysters. Strongest mortality rates appeared at that time. This study was completed by the assessment of the glycogen synthase activity in coope ration with the University of Caen. Metabolism was evaluated by a biological in vitro te st on vesleular cells located at the labial palp level. Glucose incorporation into glycogen was measured at 2 glucose concentrations (0.5 and 1.5 nmol). Incorporation rate varied from 0.13 to 1.75 nmol of glucose. A seasonal variabi lity was described. Enzymatic activity was ...